An overlooked cause of forefoot pain in athletes: Avascular necrosis of the lateral hallucial sesamoid - Jochen Gerstner Saucedo, MD; Raghav Pai, MD; Juan Bernardo Gerstner, MD (Radiology Case Reports)
Avascular necrosis (AVN) of the hallucial sesamoids is a rare and often overlooked source of forefoot pain, particularly in athletic populations. We present a case of a 39-year-old female athlete with a 1-year history of progressive pain localized to the plantar aspect of the left first metatarsophalangeal (MTP) joint. The pain had intensified over the previous 6 weeks, especially during weight-bearing activities. Notably, the patient had undergone surgical excision of the right lateral sesamoid 20 years earlier due to a similar diagnosis, which is visible on current postoperative radiographs. Radiographic imaging showed sclerosis and fragmentation of the left lateral sesamoid. MRI confirmed AVN. The patient underwent sesamoidectomy combined with a biplanar Chevron osteotomy to correct moderate hallux valgus and offload the preserved medial sesamoid. Histopathological analysis confirmed the diagnosis. The postoperative recovery was successful, with complete resolution of symptoms. This case emphasizes the necessity of including avascular necrosis in the differential diagnosis of chronic forefoot pain. The case also demonstrates the importance of combining targeted excision and realignment osteotomy in individuals with recurrent or bilateral disease to improve biomechanics and preserve joint function.